Pengaruh Gaya Kepemimpinan Kepemimpinan dan Penempatan Pegawai Terhadap Motivasi Kerja Serta Dampaknya Pada Kinerja Pegawai di Biro Umum Setda Provinsi Jambi - M Zahari MS; Fakhrul Rozi Yamali; A Irfani; Fakhrul Rozi Yamali (J-MAS (Jurnal Manajemen dan Sains), 2020)
Theoretically outlined, Employee Performance can be influenced by several variables including Leadership Style, Placement, and Work Motivation. Therefore, the performance of employees at the General Bureau of Setda Jambi Province can also be attributed to these three variables, this is what inspired the authors to conduct the research. Research objectives: 1. To find out the description of leadership style, placement,, motivation, and performance of Employees in the General Bureau of Setda Jambi Province, 2. To know the direct and indirect influence of leadership style and placement on the work motivation of employees in the General Bureau of Setda Jambi Province, 3. To know the direct and indirect influence of leadership style and placement on the performance of Employees in the General Bureau of Setda Jambi Province, 4. To know the influence of leadership style and placement through work motivation on Kinerja Employees in The General Bureau of Setda Jambi Province. This research that became the object of the research was employees of the General Bureau of Setda Jambi Province with a population of 130 people who were used as a research sample. Analysis techniques using Path Analysis tool using SPSS 22 software. The results showed that: 1. Leadership style, placement, motivation and employee performance are in good condition, 2. Leadership and placement styles directly and indirectly affect employee motivation, 3. Leadership and placement styles directly and indirectly affect employee performance, 4. Leadership and placement styles through motivation directly and indirectly affect performance.